2015
DOI: 10.3140/bull.geosci.1568
|View full text |Cite
|
Sign up to set email alerts
|

Graptolites from the Rhuddanian-Aeronian boundary interval (Silurian), Prague Synform, Czech Republic

Abstract: Forty-five graptolite species belonging to nineteen genera collected from loose rocks in the field at Všeradice and assigned to the upper vesiculosus, cyphus, triangulatus and lower pectinatus biozones of late Rhuddanian and early Aeronian age are described and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…However, the above‐mentioned genera show some variable degree of dorsal curvature. A considerable degree of dorsal curvature is typical of Coronograptus cyphus (see Štorch ) and related taxa. The genus Streptograptus (Fig.…”
Section: Constructional Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the above‐mentioned genera show some variable degree of dorsal curvature. A considerable degree of dorsal curvature is typical of Coronograptus cyphus (see Štorch ) and related taxa. The genus Streptograptus (Fig.…”
Section: Constructional Relationshipsmentioning
confidence: 99%
“…The genus Pseudopernerograptus Wang in Wang et al ., is based on species of the Monograptus revolutus group of late Rhuddanian age. Štorch () included the species referred to Pseudopernerograptus by Wang et al . () in an emended genus Pernerograptus , but was apparently not aware of the genus Pseudopernerograptus , as he did not discuss this taxon.…”
Section: Constructional Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been recognized that the earliest known Silurian retiolitine graptolites occur in the mid-Llandovery Aeronian Stage (e.g., Elles and Wood, 1908;Bouček and Münch, 1944;Obut and Sobolevskaya, 1968;Lenz and Melchin, 1987a;Melchin, 1989;Štorch, 1998). Most previous studies that document Aeronian retiolitine faunas, however, report only a single genus, Pseudoretiolites.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed study of the mid-Aeronian strata in the Czech sequence by Štorch (1998) showed that P. perlatus commonly occurs in the L. convolutus Zone, but that it also occurs rarely in the underlying Pribylograptus leptotheca and Demirastrites simulans zones (= Rastrites orbitus Subzone of Arctic Canada). Other species of Pseudoretiolites, such as P. decurtatus Bouček and Münch, 1944, and P. tianbaensis Ge, 1990 from China, first occur in most studies no lower than the L. convolutus Zone (e.g., Obut and Sobolevskaya, 1967;Štorch, 1998;Ge, 1990), or in the lowest Telychian Spirograptus guerichi and Spirograptus turriculatus zones (e.g., Bouček and Münch, 1944;Münch, 1952;Chen, 1984), although Lenz and Melchin (1987a) and Melchin (1989) Kozłowska-Dawidziuk, 2004, fig. 1), the previously known occurrence data summarized here point to the fact that this genus appeared within the lower Aeronian, but not at its base, and was relatively common in at least the mid and upper Aeronian globally.…”
Section: Introductionmentioning
confidence: 99%